(untitled) (REMUNOM, 2025)
This literature review article investigates the relationship between oblique launch, free fall motion, and quadratic polynomial functions, highlighting their importance in the teaching-learning process in high school. The work begins by investigating modeling within kinematics, addressing the motion of projectiles, with an emphasis on how the vector decomposition of velocity and the equations of motion result in the representation of a trajectory in the shape of a parabola. The study addresses the properties of the parabola and its direct implications on physical concepts, such as maximum height and horizontal range. The research discusses the importance of interdisciplinarity between Mathematics and Physics, creating a bridge between these curricular components, and emphasizes that during the teaching process, the understanding of physical phenomena must transcend the mere application of mathematical formulas. To this end, it sheds light on Mathematical Modeling and the use of digital resources, such as GeoGebra and Tracker, which are presented as instruments that promote conceptual understanding, student engagement, and reinforce the connection between theory and practice. The approaches described aim to make teaching more dynamic and attractive, in order to allow students to construct meanings and apply knowledge in everyday situations.